Primary care research - influencing and implementing into policy - Kendall Sally (Sciendo, 2021)
This editorial describes how research in primary health care can be used to influence policy. It draws on previous literature to give an example from the UK of how research in one part of primary care, the health-visiting service, has endeavoured to use evidence to influence policy and practice. The editorial considers frameworks for policy implementation such as Bardach's eight phase approach and concepts that can inform policy implementation such as Lipsky's Street-Level Bureaucrat approach.